Evaluation of Polycyclic Aromatic Hydrocarbons (PAHs) in Pork Meat Cooked with Two Different Methods - Chiara Conchione; Silvia Socal; Laura Barp; Sabrina Moret (Molecules)
During domestic grilling, polycyclic aromatic hydrocarbons (PAHs), which include genotoxic and carcinogenic compounds, can be produced as a result of fat pyrolysis, leakage of cellular juices onto the heat source, and incomplete combustion of fuel. This study aimed to assess the formation of PAHs in pork neck cooked using two different grilling methods (traditional flat grill with beech charcoal and asado grill with beech wood flame) under controlled conditions, with cooking stopping at a core temperature of 72 °C. The impact of marinating and cooking speed (fast or slow) was also evaluated over three cooking sessions. After grilling, the meat samples underwent microwave-assisted extraction, purification through solid-phase extraction (SPE), and analysis using ultra-high-performance liquid chromatography (UHPLC) with spectrofluorometric detection. Statistical analysis was performed using ANOVA (R software, version 4.3.0). None of the samples exceeded the legal limits for benzo[a]pyrene (BaP) and PAH4 (sum of chrysene, benzo[a]anthracene, BaP, and benzo[b]fluoranthene). However, the asado grill showed a significantly higher average PAH contamination (1.21 µg/kg of BaP and 3.92 µg/kg of PAH4) compared with the traditional grill (0.22 µg/kg of BaP and 1.71 µg/kg of PAH4). Marinating and cooking speed did not have a significant impact on PAH levels.